Protect the Integrity of CITES: Lessons From Japan's IWC Withdrawal to Keep Polarization From Tearing CITES Apart - Hubert Cheung; Daniel W. S. Challender; Michelle Anagnostou; Alexander R. Braczkowski; Moreno Di Marco; Amy Hinsley; Takahiro Kubo; Hugh P. Possingham; Annie Young Song; Nao Takashina; Yifu Wang; Duan Biggs (Conservation Letters)
ABSTRACT Unsustainable wildlife trade is a major driver of global biodiversity loss. Effective wildlife trade governance is critical for conservation and requires international cooperation and coordination to regulate an industry valued at hundreds of billions of dollars a year. Yet, due to increasing polarization over consumptive wildlife use, certain countries have become disenfranchised by the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), the primary mechanism for regulating international wildlife trade. Tensions within CITES are rising over the elephant ivory and rhino horn trade, where polarization has pushed ten Southern African Development Community countries to suggest an outright withdrawal from CITES. The denunciation of CITES by such a large and ecologically significant bloc would substantially weaken the integrity, credibility, and stature of the Convention. There is a contemporary precedent to reference: Japan left the International Whaling Commission (IWC) in 2019 due to polarization over commercial whaling. Here, we examine the common threads between these two cases: changing organizational ethos, polarization amongst members, influence of non‐state actors, and loss of decidability for dissenting nations. Taking critical lessons from Japan's IWC withdrawal, we propose various options for structural reforms in CITES to restore decidability, enable equitability, and implement inclusive decision‐making.